KOMPOS LIMBAH NANAS UNTUK MENINGKATKAN PERTUMBUHAN CABAI PAPRIKA - Helga, Anneta; Santoso, Handoko; Sutanto, *Agus (Universitas Muhammadiyah Metro, 2022)
Pepper cultivation has not been maximally empowered by the community because paprika chili will grow well at a temperature of 210C degrees Celsius to a temperature of 270C. This study aims to determine the effect of using compost and pumakal liquid fertilizer from pineapple waste on the growth of paprika chili from the results of article review. This research is a qualitative research with several articles related to the effect of liquid waste on the growth of paprika plants. Results Based on the research that has been done, there is a significant effect of using compost and pumacal liquid fertilizer from pineapple waste on the growth of chili peppers.